2007
DOI: 10.1007/s11199-007-9209-1
|View full text |Cite
|
Sign up to set email alerts
|

Rape Myth Acceptance Among First- and Second-Generation South Asian American Women

Abstract: Differences between European American women and first-and second-generation South Asian American women in their acceptance of rape myths were investigated. The Rape Myth Acceptance Scale, the Suinn-Lew Asian Self-Identity Acculturation Scale, and a demographic questionnaire were administered to 75 participants. A oneway analysis of variance and planned comparisons analyses showed that first-generation South Asian American women had higher rape myth acceptance than second-generation South Asian American women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
1
22
0
1
Order By: Relevance
“…This is despite Lonsway and Fitzgerald’s (1994) call for scholars to “move beyond the simple documentation of empirical relationships to the thoughtful examination of the etiology and role of rape myths in an articulated theory of culturally supported sexual aggression” (p. 159; see also Chapleau et al, 2008). For example, although research has consistently shown that men have higher levels of RMA than women (e.g., Aosved & Long, 2006; Devdas & Rubin, 2007; Franiuk, Seefelt, & Vandello, 2008; Iconis, 2008; Kassing & Prieto, 2003; McMahon, 2010; Yamawaki & Tschanz, 2005), little scholarly attention has been paid to structural reasons that underpin this finding (for two important exceptions, see Kahlor & Eastin, 2011; Suarez & Gadalla, 2010) beyond feminists’ claims that rape myths are more prevalent in male-dominant societies, which perpetuate a culture of violence (e.g., Yodanis, 2004).…”
Section: Previous Research On Rmamentioning
confidence: 99%
“…This is despite Lonsway and Fitzgerald’s (1994) call for scholars to “move beyond the simple documentation of empirical relationships to the thoughtful examination of the etiology and role of rape myths in an articulated theory of culturally supported sexual aggression” (p. 159; see also Chapleau et al, 2008). For example, although research has consistently shown that men have higher levels of RMA than women (e.g., Aosved & Long, 2006; Devdas & Rubin, 2007; Franiuk, Seefelt, & Vandello, 2008; Iconis, 2008; Kassing & Prieto, 2003; McMahon, 2010; Yamawaki & Tschanz, 2005), little scholarly attention has been paid to structural reasons that underpin this finding (for two important exceptions, see Kahlor & Eastin, 2011; Suarez & Gadalla, 2010) beyond feminists’ claims that rape myths are more prevalent in male-dominant societies, which perpetuate a culture of violence (e.g., Yodanis, 2004).…”
Section: Previous Research On Rmamentioning
confidence: 99%
“…We believe that socialization processes as well as generational effects, which we will discuss later, might account for this U‐shaped relationship. Ethnic differences with increased RMA have been found for African American [Giacopassi and Dull, 1986; Johnson et al, 1997], Hispanic [Jiminez and Abreu, 2003; Lefley et al, 1993], and Asian students [Devdas and Rubin, 2007; Lee et al, 2005] compared with Caucasian students. However, other studies found no differences [Carmody and Washington, 2001] or that existing differences vanished when level of education and socioeconomic status were controlled for [Nagel et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…44% of sexual assault victims are under age 18 and 80% are under age 30 (RAINN.org). Devdas and Rubin's (2007) number is from the National Violence against Women Survey where over 300,000 women reported having been raped in a 12-month period (701). The NCVC names sexual assault as one of the most underreported crimes with under 39% of rapes and sexual assaults ever reported to law enforcement (NCVC.org).…”
Section: Statisticsmentioning
confidence: 99%
“…Particular stereotypes develop a culture of silence around assault. Devdas and Rubin (2007) use Burt's (1980) definition of rape myths. Burt (1980) wrote that rape myths are prejudicial, stereotyped beliefs about rape, rape victims, and rapists.…”
Section: Stereotypesmentioning
confidence: 99%
See 1 more Smart Citation